Factors Affecting Investment Interest in Government Bonds for Millennial Employees in Semarang - Adinugroho, Hendi Yudhanto; Syafida, Affan Naufal; Djastuti, Indi (LifeSciFi, 2024)
This research aims to analyze the factors influencing the interest in investing in government bonds among millennial employees in Semarang City. The variables used are Motivation, Financial Literacy, and Income. The population of this study is Millennial Generation Employees residing in the city of Semarang who have an interest in investing in Government Bonds in the Indonesian Capital Market. Sample selection was conducted using the purposive sampling method. The number of samples taken in this study was 100 respondents distributed across the Semarang City area. This research uses primary data collected through structured interviews with the help of questionnaires. The data analysis used is multiple regression analysis. The conclusion drawn is that the Motivation Variable has a positive but not significant effect on the Interest in Investing in Government Bonds for Millennial Employees in Semarang City. The Financial Literacy Variable has a positive but not significant effect on the Interest in Investing in Government Bonds for Millennial Employees in Semarang City, whereas the Income Variable has a positive and significant effect on the Interest in Investing in Government Bonds for Millennial Employees in Semarang City.